1992
DOI: 10.1128/jb.174.9.2943-2950.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and killing of Escherichia coli expressing a cloned Bacillus subtilis gene whose product alters DNA conformation

Abstract: Expression of the BaciUus subtilis gene coding for SspC, a small, acid-soluble protein, caused both killing and mutation in a number of Escherichia coli B and K-12 Table 2 was with ampicillin (50 ,ug/ml); the other two plasmids were selected for with chloramphenicol (10 ,ug/ml). To construct plasmid pET-3SspC, the 0.6-kb HindIII fragment encompassing the sspC structural gene was isolated from pPS708wt. The ends of the latter fragment were filled in with the large fragment of E. coli DNA polymerase, and it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Evidence consistent with the existence of distinct domains in the membrane of growing cells of B. subtilis has been presented (49). It was also reported that the inner membrane of B. megaterium spores could be resolved into approximately equivalent amounts of two fractions of similar lipid composition, but markedly different protein content and composition (50). In contrast, the inner membrane of germinated spores gave rise to only a single fraction that had a protein content and composition intermediate between those of the two fractions from the dormant spore's inner membrane.…”
Section: Resultsmentioning
confidence: 61%
“…Evidence consistent with the existence of distinct domains in the membrane of growing cells of B. subtilis has been presented (49). It was also reported that the inner membrane of B. megaterium spores could be resolved into approximately equivalent amounts of two fractions of similar lipid composition, but markedly different protein content and composition (50). In contrast, the inner membrane of germinated spores gave rise to only a single fraction that had a protein content and composition intermediate between those of the two fractions from the dormant spore's inner membrane.…”
Section: Resultsmentioning
confidence: 61%
“…8, lanes 6, 7, and 8). Control experiments showed that the binding specificity of SspC't to pUC19 at pH 5.0 was essentially the same as at pH 7.0, as the pattern of DNase II-protected bands from pUC19 with saturating and subsaturating levels of SspCw`was identical at both pHs (27).…”
Section: Resultsmentioning
confidence: 99%
“…The question then becomes why an abasic site generated by a depurination event in spores would be cleaved rapidly. Control experiments have shown that at most 20% of abasic sites undergo strand cleavage during the extraction and nucleic acid purification procedure used (27). Consequently, if the singlestrand breaks are due to depurination, cleavage at the abasic sites must have taken place in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps regulatory approvals for some non-medical applications of phage therapy (biocontrol), which have been granted in the United States, may be of interest. The Food and Drug Administration has amended the US food additive regulations to provide for the safe use of bacteriophages on ready-to-eat meat against Listeria monocytogenes [58]. The idea that ready-to-eat meat can be treated if contaminated with Listeria bacteria, while a doctor could not get a pharmaceutical grade phage therapy product when faced with a patient suffering listeriosis, strikes these authors as absurd, especially considering the recalls of various foods due to contamination with Listeria.…”
Section: Rediscovering Phage Therapymentioning
confidence: 99%
“…The patient's symptoms ceased after a single treatment, and he made a complete recovery. Dr. d'Herelle's anti-dysentery phage was then administered to three additional patients, all of whom began to recover within 24 hours of treatment [58]. In 1923, two physicians from Baylor University's College of Medicine reported successful results from one of their phage therapy trials conducted in United States, and concluded that "the bacteriophage holds enormous possibilities as a new weapon for fighting infectious disease" [31].…”
Section: Phage Historymentioning
confidence: 99%